MEMBANGUN KEUNGGULAN BERSAING DENGAN PEMASARAN SYARIAH - Fatik Rahayu; Adiati Hardjanti; Adi Sukmanti; Fadhel Audia Yusran; Khansa Fara Wijanarko; Gunarto Gunarto (LPPM Universitas Islam 45 Bekasi, 2023)
This community service activity aims to increase understanding and skills on how to compete by implementing sharia marketing strategies. Understanding this strategy is very important as a first step in successful marketing in the future considering that there are great opportunities for implementing sharia marketing in Indonesia, where the majority of the population is Muslim. PKM activities are carried out using education, training and discussion/consultation methods. Submission of material followed by practice solving cases and continued with discussion and consultation of problems faced by participants as small business actors considered appropriate to the characteristics of PKM participants. The participants of this activity were 25 students of the Cordova College of Entrepreneurship. The activity was carried out effectively because it succeeded in increasing the participants' knowledge, understanding and skills regarding the concept of Sharia marketing.